2013
DOI: 10.1158/1535-7163.mct-13-0404
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Preferred Chemotherapeutics for Combining with a CHK1 Inhibitor

Abstract: Here we report that GNE-783, a novel checkpoint kinase-1 (CHK1) inhibitor, enhances the activity of gemcitabine by disabling the S-and G 2 cell-cycle checkpoints following DNA damage. Using a focused library of 51 DNA-damaging agents, we undertook a systematic screen using three different cell lines to determine which chemotherapeutics have their activity enhanced when combined with GNE-783. We found that GNE-783 was most effective at enhancing activity of antimetabolite-based DNA-damaging agents; however, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 37 publications
6
61
0
Order By: Relevance
“…V158411 potentiated the cytotoxicity of a range of chemotherapeutic agents in the p53 mutant colon carcinoma cell lines HT29 and Colo205 growing anchorage dependently, anchorage independently or as multi-cellular tumor spheroids (Figure 1A and 1B). The p53 mutant HT29 colon carcinoma cell line has been extensively used to evaluate the potentiation of cytotoxic chemotherapy by Chk1 inhibitors [19-23] and was therefore used as the main test system for this study. Greater potentiation was observed in both cell lines growing anchorage dependently compared to anchorage independently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V158411 potentiated the cytotoxicity of a range of chemotherapeutic agents in the p53 mutant colon carcinoma cell lines HT29 and Colo205 growing anchorage dependently, anchorage independently or as multi-cellular tumor spheroids (Figure 1A and 1B). The p53 mutant HT29 colon carcinoma cell line has been extensively used to evaluate the potentiation of cytotoxic chemotherapy by Chk1 inhibitors [19-23] and was therefore used as the main test system for this study. Greater potentiation was observed in both cell lines growing anchorage dependently compared to anchorage independently.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published studies have observed the greatest potentiation of cytotoxicity by Chk1 inhibitors with the anti-metabolite class of drugs, including gemcitabine [23]. Chk1 activity has been demonstrated to be critical for not only the DNA damage response checkpoint but also for replication fork stabilization, replication origin firing and homologous recombination.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several factors that have been implicated in conferring resistance to MAPK pathway therapeutics fall within the PI3K pathway (Figure 3). These events include the mutation of PIK3CA, loss of the PTEN and INPP4B tumor suppressors, in premature entry into mitosis with damaged DNA and subsequent mitotic catastrophe and cell death (97,98). Kinase inhibitors can also be used to mitigate the effects of cytotoxic agents on rapidly proliferating normal tissue.…”
Section: Drug Combinations Converging On a Hallmark Characteristic Ofmentioning
confidence: 99%
“…Clearly these are important factors that can dictate tumor growth and affecting these processes could contribute to the efficacy observed. 36 Our studies used gemcitabine because it is a major modality of treatment for pancreatic cancer patients. However, we believe that the choice of which chemotherapy to be used along with bosutinib or Bos-I should be explored further.…”
Section: Discussionmentioning
confidence: 99%